Kebugaran Jasmani dan Perkembangan Ilmu Pengetahuan dan Teknologi dalam Masyarakat - Arma Abdoellah (Jurnal Pendidikan Jasmani Indonesia, 2005)
Development of science and technology brings alteration from active way tonon-active or having a lot of sit way of life. It is caused by machine replaces work thatpreviously done used muscle strength. This non-active way of life brings about hipokinesa disease that is one of cause of heart, hypertension, stroke and obesity diseases. Tomaintain physical hale and hearty, students, employee, old age man and other groupof society need to do physical activities regularly. Reality shows that globalization occurin the campaign improving physical hale and hearty.Although in America movement to improve hale and hearty has begun in 1965 wasfully-supported by the presidents, result of survey showed that after 15-years-done,physical healthy level of participants did not increase, even tend to decrease. The causewas physical education program which was done did not support to maintain and toimprove physical hale and hearty level. The movement of physical hale and heartywas proclaimed by President Soeharto in state speech with sport slogan “memasyarakatkan olahraga dan mengolahragakan masyarakat”. Reality shows that populationof cities in Indonesia are much aroused to do physical activities. And, as in America, itcan be predicted that physical education program in Indonesia is also cannot maintainand improve physical hale and hearty of participants because educational institutionin Indonesia does not have sport facilities and equipment as developed countrieshave. This constitutes a challenge for physical education teacher and related institution.There are enough evidences that hale and hearty program in work places resultsadvantages such as reducing healthy maintenance cost of employee, number of employee’s absence in work time, work spirit of employee and also increasing productivity.In Indonesia this program needs to be encouraged in every company by providingthose sport facilities and equipments. Employee is an important and vital asset forcompany and government or private institution.The more prosperity of population in one country as consequences of developmentheld, the more the member of old age population increased. To make old age population not be a burden to government and society in maintaining their health, it needsan attempt to improve their hale and hearty by carrying out physical activities programthat is adjusted to them and is managed by professional staff. There should be educational institutions that produce professional staff to manage hale and hearty programfor employee and old age man.Keyword: Physical Activities, Science and Technology.